Mobilidades vulneráveis: acidentes de trânsito na Metrópole de São Paulo - (:unkn) unknown (Revista Transporte y Territorio, 2016)
Para acceder al Artículo utilice el link: http://revistascientificas.filo.uba.ar/index.php/rtt/article/view/2858
This article aims to understand the most current problems of mobility in everyday life of the metropolis of São Paulo, which expands in the 1990s onwards, product of the popularization of private individual transport, especially related to the advent of popular car and to the bigger facility of the motorcycle purchase , resulting, among other problems, in the expansion of traffic accidents. Therefore, this article is based on analysis of data from the Mortality Information System (SIM) of the Ministry of Health in the period of 1980-2011, related to traffic accidents in Brazil, with a particular focus in the metropolitan region of São Paulo.
Este artigo visa compreender os problemas mais atuais da mobilidade no cotidiano da metrópole de São Paulo, que se amplia na década de 1990 em diante, produto da popularização do transporte individual privado, especialmente, relacionado ao advento do carro popular e a maior facilidade de se adquirir a motocicleta, resultando,entre outros problemas, na ampliação dos acidentes de trânsito. Para tanto, este artigo baseia-se na análise dos dados do sistema de Informações sobre mortalidade (SIM) do Ministério da Saúde, no período compreendido de 1980 a 2011, referente aos acidentes de trânsito no Brasil, com enfoque particular na região metropolitana de São Paulo.
Fil: Barbosa da Silva, Ricardo. Faculdade de Tecnologia do Estado de São Paulo. Fundação Santo André; Brasil.
Keywords: mobility; transport; traffic-accidents; Brasil; São Paulo; movilidad; transporte; accidentes de tránsito; Brasil; San Pablo